Binary Solvent-assisted Graphene Synthesis by Direct Exfoliation of Graphite Powder and its Cytotoxicity on SiHa Cell Line - Kumar, Prabhat; Jain, Purnima; Sarkar, Anjana (Indian Journal of Pharmaceutical Education and Research, 2022)
A cost-effective mass production of pristine graphene nanosheet is still an important challenge to harness its maximum potential in medical sciences. Here, we have used a binary solvent mixture of low dielectric constant (1,2,4- trichlorobenzene,ε = 2.24 and benzylamine,ε = 4.6) to produce a high quantity (0.6 mg/ml) of graphene under ultrasonication without compromising its quality. Obtained sample were characterized through XRD, UV-Vis, Raman, FT-IR, TEM-SAED, and cytopotency was evaluated on SiHa cell line. IG/I2D < 1.0 (~ 0.39) was achieved on more than 250 μm2 area, indicating the uniformity and obtained ID/IG ratio was 1.21. No toxicity was found in the case of 24 hr on the SiHa cell line. EC50 computation was 84.90 μg /ml for 48 hr and 62.03 μg /ml for 72 hr. Exfoliated graphene remained stable in binary solvent even after 1 year. The proposed experiment and obtained data can be powerful tools to explore the synergic effect of binary solvent exfoliation in combination to establish graphene as a biomaterial for neuronal network, tissue engineering, drug delivery, and regenerative medicines, to name a few.
Keywords: Graphene; Nanosheet; Cytotoxicity; SiHa Cell line; Biomaterial